2015
DOI: 10.1002/adma.201502276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Size, Electronic Connectivity, and Incoherent Nanoscale Domains on the Sequence of Lithiation in LiFePO4 Porous Electrodes

Abstract: High-resolution X-ray microscopy is used to investigate the sequence of lithiation in LiFePO4 porous electrodes. For electrodes with homogeneous interparticle electronic connectivity via the carbon black network, the smaller particles lithiate first. For electrodes with heterogeneous connectivity, the better-connected particles preferentially lithiate. Correlative electron and X-ray microscopy also reveal the presence of incoherent nanodomains that lithiate as if they are separate particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(127 citation statements)
references
References 55 publications
7
115
0
3
Order By: Relevance
“…Afterwards, we could confirm many individual nanoparticles with uniform single-crystal like orientation exhibiting both, LFP and FP phases, in agreement with published experimental observations [4,5,14,16] and theoretical modellings [25,26], especially a recent in-situ X-ray study confirmed the coexistence of both phases (LFP+FP) in individual single crystalline particles [27]. Some of the particles in figure 1a containing both phases are shown in detail in figure 2.…”
Section: Crystallographic Analysis Of the Acom-tem Data: Properties Osupporting
confidence: 77%
See 2 more Smart Citations
“…Afterwards, we could confirm many individual nanoparticles with uniform single-crystal like orientation exhibiting both, LFP and FP phases, in agreement with published experimental observations [4,5,14,16] and theoretical modellings [25,26], especially a recent in-situ X-ray study confirmed the coexistence of both phases (LFP+FP) in individual single crystalline particles [27]. Some of the particles in figure 1a containing both phases are shown in detail in figure 2.…”
Section: Crystallographic Analysis Of the Acom-tem Data: Properties Osupporting
confidence: 77%
“…Transmission electron microscopy (TEM) offers various sophisticated methods for LiFePO 4 /FePO 4 (LFP/FP) phase mapping with high spatial resolution [6][7][8][9][10][11][12][13][14][15][16]. The mapping methods can be sorted into two families: one are spectroscopy methods based on the chemical information encoded in the energy spectra; the other are diffraction methods relying on the crystallographic information recorded in diffraction patterns or high resolution (HR)TEM images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the geometric area and thickness of the electrode, LFP density and assuming a nominal capacity of āˆ¼170 mAh g āˆ’1 , the total volume fraction of LFP is estimated to be 0.39. Assuming āˆ¼10 vol.% of the electrode is filled with binder and conductive material in the LFP electrode, 43 the porosity of the LFP electrode is then calculated to be āˆ¼0.51. The rate constant for the electrode reaction at the surface of the Li foil has been measured using Li/Li symmetric cells, as reported in a previous study.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 In summary, three major lithiation/delithiation mechanisms have been proposed: i) intra-particle phase transformation causing mechanical damage (incoherent or semi-coherent), [32][33][34][35] ii) intra-particle phase transformation with no mechanical damage (coherent) 33 and iii) interparticle phase transformation in an ensemble of electronically and ionically connected particles which are present in a solid-solution phase away from equilibrium. [29][30][31][36][37][38][39] The dominant mechanism is determined by factors such as particle size and shape, 33,42 quality of ionically and electronically conductive coatings, synthesis route, structural defects, electrode formulation and microstructure, 43 temperature, applied potential/current 38,39 and the conditioning cycles or the cycling history. 32 Core-shell-type 14,44 and non-ideal solid-solution 26,27 models have been used to describe the juxtaposition of the two phases in a single particle observed during chemical lithiation/delithiation.…”
mentioning
confidence: 99%